Effect of Maize (Zea mays L.) and Legume Intercropping Systems on Weed Dynamics - Singh, Chongtham Roben; Longkumer, L. Tongpang (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted during two consecutive seasons of kharif (June to October), 2016 and 2017 at the Experimental Research Farm, ICAR Research Complex for NEH Region, Nagaland Centre, Medziphema, Nagaland, India. The treatments consisted of four planting geometries i.e. maize+black gram (1:1), maize+black gram (2:2), maize+soybean (1:1) and maize+soybean (2:2) and three weed management practices i.e. weedy check, pre-emergence application of pendimethalin @ 1.0 kg a.i. ha-1+one hand weeding (1HW) at 30 DAS and two hand weedings (2HW) at 20 and 40 DAS. The experiment was laid out in Randomized Block Design with two factors comprising twelve treatment combinations and replicated three times. The results revealed that among the planting geometry, maize+soybean (2:2) recorded the highest weed control efficiency (WCE) and reduced the weed population, fresh weight and dry weight of monocot and dicot weed at 60 DAS and gave the maximum maize equivalent yield (4374.96 kg ha-1). Among the weed management, 2HW at 20 and 40 DAS recorded the lowest weed population, fresh weight, dry weight and the highest weed control efficiency (WCE) of monocot and dicot weed at 60 DAS and the maximum maize equivalent yield as 4591.10 kg ha-1 which was at par with the pre-emergence application of pendimethalin @ 1.0 kg a.i. ha-1+1HW at 30 DAS as 4461.80 kg ha-1. The highest net return (Rs. ha-1), return per rupee invested and B: C ratio were recorded from the pre-emergence application of pendimethalin @ 1.0 kg a.i. ha-1+1HW at 30 DAS with ` 36624.05 ha-1 which was closely followed by 2HW at 20 and 40 DAS with Rs. 35428.81 ha-1.